Strategic Response to Industry 4.0; In the Perspective of Technology-Organization Environment and Emotional Intelligence - Soharwardi, Mariam Abbas; Fayyaz, Sana; Rahman, Haji; NomanShafique, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
Technology-Organization-Environment (TOE) framework is the organizational level theory that suggests the acceptance and implementation of new and advanced technologies in the organization. In this study, the strategic response to industry 4.0 has been focused. This study will answer; how organizations can strategically respond to industry 4.0, which is the latest industrial revolution. Moreover, this study has considered the emotional intelligence individual-level factor to implement new technologies in the organization, which will enable organizations to strategically response the industry 4.0 The population of this study is the Chinese manufacturing industry. The sample size is 250, which was collected through a simple random sampling method. Data has been collected through the survey method. The advanced statistical software PLS-SEM has used for structural equation modelling for analysis. Structural equation modelling consists of two modellings; measurement model and structural model. In the measurement model, reliability and validity through Cronbach alpha, composite reliability, average variance extract (AVE), and factor loadings of data have been measured. After the measurement model structural model based on the path coefficient through explanatory factor (R2) with significant values has been mentioned. The results are in favour of the proposed model; only the moderating effect is contradicting, while emotional intelligence is playing its role as an independent variable instead of a moderating effect. The advancement of IT technologies has evolved the industries into industry 3.0 to industry 4.0. Now a day’s organizations are using advanced technologies in their production and manufacturing, which has integrated all the machines and processes through networking, or the internet. It will change the production concept to smart production. So, the manufacturing organizations can survive only, if they respond to the industrial revolution towards the industry 4.0. This study has contributed to the literature through emotional intelligence and highlighted the most important technological, organizational, and environmental factors to respond to industry 4.0; those are more practically implemented in the manufacturing companies.